Spatial and Seasonal Variation of Doline Water Hydrochemistry in West Gunungsewu Karst Area, Yogyakarta Special Region, Indonesia - Listyani R.A., T.; Ridayati (UIR PRESS, 2024)
The doline water hydrochemical study was conducted in the Gunungsewu karst area, Yogyakarta Special Region. The hydrogeological survey followed by doline water sampling was carried out in the Panggang and Wonosari-Baron Hydrogeological Subsystems. Ten selected doline water samples were taken, each in the dry and rainy season, for further physical/chemical testing in the laboratory. Research analysis includes hydrochemical analysis of several parameters such as pH, TDS, EC, major and minor ions content and assisted by difference and variability tests statistical analysis. The hydrochemical variations of doline water in the study area generally did not show any spatial variations, except for the EC parameter. Temporal/seasonal hydrochemical variations are apparent, as evidenced by differences in many variations of TDS, EC, major ions (Ca2+, Na+, K+, HCO3-, Cl-), and minor ions (sulfate and nitrate). In the dry season, the hydrochemical facies generally develop as Ca, Na-bicarbonate facies, while in the rainy season, doline water typically has Ca-bicarbonate facies. The hydrochemical of doline water may be influenced by groundwater.